Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

Flotation mechanism of an amide-based fatty acid collector for quartz ore: A gene-matching perspective - Wenda Guo; Baida Chen; Zhenyue Zhang; Sicheng Li; Han Zhang; Heng Zhang; Hanjun Wu; Defeng Liu (Minerals Engineering, 2026)

Development and validation of CFDT code for fission product release analysis of spherical and cylindrical TRISO-based fuel element in HTGRs - Liying Zhang; Defeng Yang; Xiaoxia Wang; Aijun Mi; Guoming Liu; Liangzhi Cao; Jinkai Liu; Shiyu Liu; Pengpei Xie; Qingmin Zhang (Annals of Nuclear Energy, 2026)

Evaluation of an Automated Vaccination Strategy Against Aeromonas hydrophila in Grass Carp: A Comparative Study with Conventional Manual Injection - Lin Luo; Zhen Qin; Chen Li; Defeng Zhang; Yan Ren; Qing Wang; Jian Zhao; Songming Zhu; Zhangying Ye (Fishes, 2026)
(1) Background: Vaccination is crucial for Ctenopharyngodon idella, yet the impact of delivery methods on welfare and immunity requires investigation. (2) Methods: This study compared manual (HI-V) and automated (AI-V) injections of inactivated Aeromonas hydrophila vaccine. (3) Results: Both methods induced protective immunity, with AI-V achieving a slightly higher Relative Percent Survival (41.67%) than HI-V (37.84%). AI-V promoted stable erythropoiesis and robust systemic/mucosal IgM responses with elevated HSP70 and IL-6. Conversely, HI-V triggered sharp transient stress and upregulated Gadd45γ, indicating greater genotoxic stress. (4) Conclusions: Automated injection offers comparable immune protection with reduced physiological stress and improved homeostasis, supporting its use for welfare-conscious aquaculture.

Microplastic accumulation in paired human breast tumor and para-tumor tissues and exploratory clinical associations - Limin Jia; Yanni Song; Yufeng Guo; Fuyu Yang; Qiyan Guan; Weihan Zhang; Yang Liu; Defeng Xing; Yanhong Lv (Journal of Hazardous Materials, 2026)

Synergistic hydroxyl and chlorine radicals in contact-electro-catalysis for sustainable PFAS remediation - Jin Zhang; Wei Li; Jinxing Ma; Jianghu Cui; Kuanchang He; Kui Yang; Qian Liu; Min Zhang; Sihao Lv; Faliang Cheng; Defeng Xing (Journal of Hazardous Materials, 2026)

Performance evaluation of building-integrated photovoltaic windows with triple-glazing: Summer assessment in cold climate - Chunwen Xu; Xintao Tian; Rumei Yang; Shasha Song; Fei Han; Defeng Kong; Yelin Zhang (Energy and Buildings, 2026)

Solar-driven dye wastewater purification and synergistic desalination by an aerogel-based multitasking platform structured with polydopamine-hybridized covalent organic frameworks - Feng Wang; Zequan Shen; Hui Wang; Yuheng Zhang; Baoxia Dong; Defeng Wu (Journal of Hazardous Materials, 2026)

Chlorocholine chloride delays progenitor Leydig cell differentiation via PI3K/AKT pathway activation in rats - Haoran Zhang; Yijia Li; Xiaoxia Wang; Chenping Kang; Qiong Zhang; Defeng Liu; Jiaming Mao; Qianqian Xiao; Weidong Hao (Toxicology, 2026)

Synthesis and mechanistic insights of α-chlorinated lauric acid as a high-efficiency collector for apatite flotation - Wenda Guo; Heng Zhang; Zhenyue Zhang; Haolong Lu; Defeng Liu; Hanjun Wu (Minerals Engineering, 2026)

Effect of particle size on debris avalanche-induced river blockage by laboratory-scale experiments - Hao Wu; Defeng Zheng; Fang Zhang; Tingkai Nian (Landslides, 2026)

Development of a Sensitive Real‐Time PCR Method for Detection of Carp Oedema Virus - Huilin He; Ruixue Feng; Siyi Guo; Bing Han; Jinshan Huang; Xu Lin; Jiyuan Yin; Defeng Zhang; Min Liu; Wen Shi (Journal of Fish Diseases, 2026)
Carp oedema virus disease (CEVD), caused by the carp oedema virus (CEV), results in significant economic losses to the common carp and koi aquaculture industry. The CEVD symptoms resemble those of koi herpesvirus (KHV) and include lethargy, swollen gills, sunken eyes, and skin haemorrhages. Consequently, the development of efficient detection methods is imperative for the prevention and diagnosis of CEVD. In this study, we developed a quantitative real‐time PCR assay for the sensitive detection of CEV infection. Specific primers were designed based on a highly conserved region within the CEV p4a gene. The assay exhibited a sensitivity that was 100‐fold greater than that of the conventional PCR technique, with high specificity, and no observed cross‐reactivity with infectious haematopoietic necrosis virus (IHNV), infectious pancreatic necrosis virus (IPNV), spring viremia of carp virus (SVCV), salmonid alphavirus (SAV), or KHV. Inter‐ and intra‐assay experiments also confirmed the method's high repeatability. In a clinical setting, it showed higher sensitivity compared to the diagnostic methods for CEVD developed by the Center for Environment, Fisheries and Aquaculture Science (CEFAS), while also significantly reducing detection costs. Consequently, the established assay could provide robust technical support for the clinical diagnosis and epidemiological investigation of CEVD.

Sesquiterpenoids from Euphorbia esula L. - Defeng Yan; Miaomiao Zhang; Dan Tang; Yuqing Song; Liu Liu; Haiqing Zhao; Nurmirza Begmatov; Orzimat Turdimatovich Turginov; Bo Zhao; Hequn Yang; Guoan Zou (Phytochemistry, 2026)

Charge-specific impacts of polystyrene nanoplastics on acidogenesis and biofilm adaptation in Ethanoligenens harbinense - Jing Wang; Weimin Zhu; Xingze Zhang; Sitong Liu; Jun Ma; Defeng Xing (Bioresource Technology, 2026)

Rare Bacterial Taxa Drive Soil Multifunctionality in Lakeside Wetlands of Eutrophic Lake - Lingchen Yuan; Jiajia Zhang; Mengxi Gao; Renlei Yang; Yue Chen; Bin Hu; Defeng Feng; Wei Li (Wetlands, 2026)

Identification of a NEK7-related pyroptosis gene signature against pancreatic cancer and evaluation of its potential in tumor microenvironment remodeling via regulating inflammasome complex - Jia Liu; Zilong Yan; Tongning Zhong; Jianhua Qu; Defeng Lei; Jinglin Lai; Citing Zhang; Zhengquan Lai; Weipeng Ai; Xueqing Liu (Functional & Integrative Genomics, 2025)

Physiological stress and tissue damage response of Ctenopharyngodon idella to artificial and automated injection - Lin Luo; Zhen Qin; Chen Li; Defeng Zhang; Yan Ren; Qing Wang; Chenqing Zhang; Songming Zhu; Zhangying Ye (Aquaculture International, 2025)

Effect of myofibrillar protein structure changes mediated by NaCl on the binding capacity of volatile compounds in Cantonese sausage - Yuanhong Zhang; Defeng Zeng; Shihong Cai; Qiaoyu Liu; Weizheng Sun; Xin Hu; Hui Peng; Hao Dong; Xiaofang Zeng (Food Chemistry, 2025)

Self-regulating adaptability of biofilm microbiomes enhances manganese and ammonia removal in microbial electrochemical filters under dioxane exposure - Sitong Liu; Kun Feng; Dawei Zhang; Yang Liu; Jing Wang; Baiyun Lu; Defeng Xing (Journal of Hazardous Materials, 2025)

Krϋppel-like factor 12a and 12b inhibit Cyvirus cyprinidallo3 replication by repressing viral ORF8 promoter activity - Xinyue Hu; Yingying Li; Yingying Wang; Defeng Zhang; Donghai Liu; Qing Wang; Shucheng Zheng (Fish & Shellfish Immunology, 2025)

Sesquiterpenoids from Ferula samarkandica - Miaomiao Zhang; Mayire Nueraihemaiti; Khamidulla Kamoldinov; Defeng Yan; Yuqing Song; Nannan Xu; Guoan Zou; Haji Akber Aisa (Phytochemistry, 2025)

Reassessing systemic blind spots in modern water disinfection paradigms - Yang Liu; Jialiang Gu; Kun Feng; Yangyang Zhang; Zheng Zhong; Sitong Liu; Defeng Xing (Journal of Hazardous Materials, 2025)

Migration law of micro-fine particles and enhancement of leaching process in weathered crust elution-deposited rare earth ores - Defeng Liu; Shijia Zhang; Zhenyue Zhang; Wenda Guo; Ruan Chi (Minerals Engineering, 2025)

Introducing transition metal cations to promote the oxygen reduction kinetics of double perovskite as SOFC cathode - Jie Yang; Yaping Zhang; Xiaofei Zhu; Jinghe Bai; Shangyu Li; Wenfu Yan; Defeng Zhou (Chemical Engineering Journal, 2025)

Precise baseline determination for the four-satellite InSAR constellation HT-01 with ambiguity resolution constraints - Dachen Peng; Shibo Guo; Defeng Gu; Kai Shao; Houzhe Zhang; Ruiyun Yang; Jufeng Lu; Jiangkai Liu; Haoseng Wang; LiuPeng Huang (Advances in Space Research, 2025)

A method for improving the BDS3-based kinematic precise orbit determination of LEO satellites with single-receiver ambiguity resolution - Houzhe Zhang; Defeng Gu; Kai Shao; Bing Ju; Bin Yi; Zhiyong Huang; Haijun Tao (Advances in Space Research, 2025)

Methyltransferase HsdM Regulates the Pathogenicity of Streptococcus agalactiae to Nile Tilapia (Oreochromis niloticus) - Dongdong Jiang; Bei Wang; Yan Ren; Xubing Mo; Meiling Yu; Defeng Zhang (Fishes, 2025)
DNA methylation is a critical mechanism for regulating gene expression in bacteria and plays an essential role in bacterial pathogenesis. A mutant, WC1535ΔhsdM, lacking hsdM encoding a DNA methyltransferase was constructed using homologous recombination technology. The growth, hemolytic activity, and capsule formation of the mutant were analyzed. The dynamic distribution of the wild-type (WT) and mutant strains in tilapia tissues after artificial infection was determined. The adhesion, invasion, anti-phagocytic, and whole-blood survival abilities of the WT and mutant strains were analyzed. Tilapia were intraperitoneally injected with the WT or mutant strains, and the LD50 values were determined. The expression levels of the immune-related genes in tilapia were analyzed by qRT-PCR. The mutant showed faster growth during the logarithmic growth period (5–10 h) and lower hemolytic activity than the WT strain. Mutant loads in tilapia tissues were significantly lower than those of the WT strain. Mutant strain adhesion to epithelial cells was significantly reduced, it was more easily engulfed by macrophages, and it had decreased intracellular survival. The LD50 of the mutant was 2.06 times higher than that of the WT strain, indicating decreased pathogenicity. Expression levels of immune-related genes IL-1β, IL-6, IFN-γ, and TNF-α in tilapia induced by the mutant were lower than those by the WT strain. In conclusion, the WC1535ΔhsdM mutant exhibited an increased growth rate and decreased hemolytic activity, tissue colonization, and pathogenicity, indicating that HsdM could regulate S. agalactiae growth and pathogenicity. This study provides new insights into the pathogenesis of piscine S. agalactiae.

Enhancement of mass transfer process in column leaching by graded combination of coarse–medium–fine (C–M–F) particle packing: Application to heap leaching of ion-adsorption type rare earth ore with mixed (NH4)2SO4 and NH4Cl solution - Defeng Liu; Yuzhi Wang; Zhenyue Zhang; Ruan Chi (Hydrometallurgy, 2025)

CoOX composite Pr0.4Sr0.6Co0.2Fe0.8O3-δ perovskite was used to obtain an IT-SOFC cathode with high electrocatalytic activity - Yuqian Wang; Defeng Zhou; Weiyi Zhang; Jie Yang; Qingyuan Sheng; Xiaofei Zhu; Jinghe Bai (Fuel, 2025)

Differentiation of the Anammox core microbiome: Unraveling the evolutionary impetus of scalable gene flow - Quan Zhang; Xiao-Ming Ji; Xueting Wang; Wei Wang; Xijun Xu; Qi Zhang; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Water Research, 2025)

Designing and evaluating a novel blood-brain barrier in vitro model of teleost for reproducing alterations in brain infecting - Yanghui Chen; Yi Li; Wenze Li; Yuan Li; Defeng Zhang; Yu Huang; Jia Cai; Eakapol Wangkahart; Jichang Jian; Bei Wang (Fish & Shellfish Immunology, 2025)

Precise baseline determination for InSAR formation-flying satellites based on spaceborne BDS-3 and GPS observations - Dachen Peng; Kai Shao; Defeng Gu; Houzhe Zhang; Zhiyong Huang; Bin Yi; Jubo Zhu (Advances in Space Research, 2025)

Sulfur cycle-mediated biological nitrogen removal and greenhouse gas abatement processes: Micro-oxygen regulation tells the story - Yu Zhang; Wei Wang; Xijun Xu; Quan Zhang; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Chuan Chen (Bioresource Technology, 2024)

Linking performance to dynamic migration of biofilm ecosystem reveals the role of voltage in the start-up of hybrid microbial electrolysis cell-anaerobic digestion - Xue-Ting Wang; Lei Zhao; Quan Zhang; Bo Wang; Defeng Xing; Jun Nan; Nan-Qi Ren; Duu-Jong Lee; Chuan Chen (Bioresource Technology, 2024)

Development of CadR-based cadmium whole cell biosensor for visual detection of environmental Cd2+ - Tianyi Zhang; KaiLi Zhu; Xia Zhang; Xin Yu; Liang Shen; Defeng Gao; Yiwen Chen; Qinghua Wang; Shaopeng Chen; Lingzhi Bao (Analytica Chimica Acta, 2024)

Editorial: Advances in autonomous ships (AS) for ocean observation - Xinyu Zhang; Yanlong Chen; Gorka Bidegain; Defeng Wu; Yanzhen Gu; Chengbo Wang (Frontiers in Marine Science, 2024)

Integrated transcriptome and metabolome profiles reveal the regulatory molecular mechanisms of meat quality in pasture-fed goose - Qasim Ali; Boshuai Liu; Shaokai La; Umar Farooq; Yao Han; Mengqi Liu; Yan Zhang; Defeng Li; Zhichang Wang; Hao Sun; Yalei Cui; Sen Ma; et al. (Food Bioscience, 2024)

Fluorocarbon polymers mediated contact-electro-catalysis activating peroxymonosulfate for emerging pollutants degradation: The key role of fluorine density in electron transfer - Dongmei Ma; Wei Li; Jin Zhang; Kuanchang He; Changyong Zhang; Gang Wang; Xiaodong Xin; Qian Liu; Faliang Cheng; Sihao Lv; Defeng Xing (Chemical Engineering Journal, 2024)

Microbiome and antibiotic resistome in bioelectrochemical toilets for onsite treatment of fecal sludge - Xiaoyu Cai; Huihui Zhou; Yu Lou; Baiyun Lu; Dawei Zhang; Jing Wang; Defeng Xing (Water Research, 2024)

A comparative study on the taste quality of whiteleg shrimp (Penaeus vannamei) under two different transportation strategies - Zhihai Huang; Weiliang Guan; Defeng Xu; Xiamin Lyu; Nanfeng Tan; Yongjun Xu; Xiasen Zhang; Ming Fang; Linchun Mao (Food Bioscience, 2024)

Baicalin attenuates aflatoxin B1-induced hepatotoxicity via suppressing c-Jun-N-terminal kinase-mediated cell apoptosis - Defeng Wen; Jie Zhang; Hualin Zhou; Yinsheng Qiu; Pu Guo; Qirong Lu; Jianglin Xiong (Mycotoxin Research, 2024)

Development of real‐time recombinase polymerase amplification ( RPA ) and RPA combined with lateral flow dipstick ( LFD ) assays for the rapid and sensitive detection of cyprinid herpesvirus 3 - Yingying Li; Ruifan Li; Xubing Mo; Yingying Wang; Jiyuan Yin; Sven M. Bergmann; Yan Ren; Houjun Pan; Cunbin Shi; Defeng Zhang; Qing Wang (Journal of Fish Diseases, 2024)
In this issue, we established rapid, cost‐effective, and simple detection methods including recombines polymerase amplification with lateral flow dipstick (RPA‐LFD) and real‐time RPA for cyprinid herpesvirus 3(CyHV‐3), and evaluated their sensitivity, specificity, and applicability, the real‐time RPA method could achieve sensitive diagnosis of CyHV‐3 within 1.3 copies per reaction, respectively. The real‐time RPA method is 10‐fold more sensitive than RPA‐LFD method. The exact number of CyHV‐3 can be calculated in each sample by real‐time RPA. The sera from koi also can be tested in these methods. In addition, no cross‐reaction was observed with other related pathogens, including carp oedema virus (CEV), spring viraemia of carp virus (SVCV), cyprinid herpesvirus 1(CyHV‐1), cyprinid herpesvirus 2(CyHV‐2), type I grass carp reovirus (GCRV‐I), type II GCRV (GCRV‐II), type III GCRV (GCRV‐III), and Aeromonas hydrophila.

A hydrogel-modified electrochemical biosensor for the rapid detection of ammonia‑nitrogen-resistant bacteria - Ting Zhang; Sayeda A. Abdelhamid; Defeng Li; Houjin Zhang (Science of The Total Environment, 2024)

Overlooked in-situ sulfur disproportionation fuels dissimilatory nitrate reduction to ammonium in sulfur-based system: Novel insight of nitrogen recovery - Bo Shao; Li Niu; Yuan-Guo Xie; Ruochen Zhang; Wei Wang; Xijun Xu; Jianxing Sun; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Zheng-Shuang Hua; Chuan Chen (Water Research, 2024)

Dating Kimberlite Using Apatite U-Pb Geochronology: A Case Study from Diamond-Bearing Dikes in South China - Jiawei Zhang; Huan Wang; Defeng He; Yuhua Zhu; Kun Wang; Yuan Qiu (Journal of Earth Science, 2024)

Techno-economic evaluation of a seawater source heat pump system with auxiliary heat source in cold region of China - Luhang Wang; Chunli Wang; Chunwen Xu; Lancai Zhang; Huan Su; Defeng Kong (Energy and Buildings, 2024)

Water-saving irrigation and delayed sowing increased the emission intensity of CH4 and N2O in the rice-wheat rotated field under nighttime warming - Yunsheng Lou; Jun Li; Junhong Guo; Defeng Pan; Zhen Zhang; Li Ma; Rui Li; Lixuan Ren (Agriculture, Ecosystems & Environment, 2024)

A high-performance composite cathode based on thermal expansion complementation for SOFC - Ling Hu; Defeng Zhou; Xiaofei Zhu; Ning Wang; Jinghe Bai; Huifang Gong; Youjie Zhang; Yunlong Chen; Wenfu Yan; Qiurong Zhu (Fuel, 2024)

Coxsackievirus and adenovirus receptor inhibits tilapia lake virus infection via binding to viral segment 8 and 10 encoded protein - Jing Wen; Zishan Ke; Yingying Wang; Yingying Li; Defeng Zhang; Xubing Mo; Jiyuan Yin; Cunbin Shi; Wenli Zhou; Shucheng Zheng; Qing Wang (Fish & Shellfish Immunology, 2024)

A novel study of brain microvascular endothelial cells induced by astrocyte conditioned medium for constructing blood brain barrier model in vitro: A promising tool for meningitis of teleost - Yanghui Chen; Yuan Li; Junliang Luo; Zixin Li; Yu Huang; Jia Cai; Dongneng Jiang; Defeng Zhang; Jichang Jian; Jun Qiang; Bei Wang (Fish & Shellfish Immunology, 2024)

Recycling different crystal forms of MnO2 from spent Li-ion batteries cathodes for SDZ degradation - Xinxin Lv; Fang Deng; Huilai Liu; Yu Zhang; Qingjun Liu; Yueqing Liang; Defeng Kong; Mukhtar Ahmad; Xing Chen (Journal of Environmental Chemical Engineering, 2024)

The Bacillus velezensis CYS06 Strain Exhibits Promising Applications in Fighting Grass Carp Bacterial Diseases - Lijuan Liu; Dongdong Jiang; Yan Ren; Cunbin Shi; Yajun Wang; Jiyuan Yin; Qing Wang; Defeng Zhang (Fishes, 2023)
Aeromonas septicemia and columnaris disease are major bacterial diseases in grass carp; however, the drugs currently used to control these diseases pose environmental and health risks. This study aimed to screen for a probiotic Bacillus strain with antagonistic activity to prevent and control bacterial diseases in grass carp and to evaluate the antimicrobial activities, biosafety, and biocontrol effects of this strain. A Bacillus strain with antagonistic activity against Aeromonas hydrophila, obtained from grass carp intestines, was screened, and the isolate CYS06 was identified by analyzing the 16S rRNA and gyrA gene sequences. The antimicrobial spectrum of the strain CYS06 was determined, and the activities of amylase, cellulase, protease, and lipase of the strain CYS06 were determined. The whole genome of the strain CYS06 was sequenced using the nanopore sequencing technology platform, followed by the analysis of the antagonistic substance synthesis gene clusters and CAZy enzyme gene families. The biosafety of the strain CYS06 was evaluated via intraperitoneal injection into healthy grass carp. After the strain CYS06 was fed to the grass carp, its biological control effect on this fish was evaluated through artificial infection experiments. The strain CYS06 was identified as Bacillus velezensis, based on molecular identification, which shows broad antimicrobial activity against various fish pathogens. The strain CYS06 secretes amylase, cellulase, protease, and lipase. The genome size of the strain CYS06 is 3,914,159 bp, and it contains eight antagonistic substance synthesis gene clusters and many CAZy enzymes. The strain CYS06 exhibits high biological safety for grass carp, based on the challenge test. Feeding grass carp with the strain CYS06 for 4 weeks significantly enhanced the resistance of the fish to A. hydrophila. Strain CYS06 could inhibit the growth of Flavobacterium columnare under co-culture and reduce the amount of F. columnare adherence on the gills of grass carp, indicating that CYS06 has good potential for the prevention and control of columnaris disease. In conclusion, we isolated an antagonistic probiotic strain, CYS06, which exhibits a biological control effect on septicemia and columnaris disease caused by Aeromonas spp. and F. columnare in grass carp, respectively. This strain contains many antagonistic substance synthesis-related gene clusters and holds the potential to degrade various types of carbohydrates. As a biological control agent, the strain CYS06 exhibits significant potential for the prevention and control of bacterial diseases in grass carp.

Investigation into the treatment and resource recovery of rifamycin mycelial dreg with thermal alkaline pretreatment-anaerobic digestion - Quan Zhang; Xuejiao Gong; Yu Zhang; Xueting Wang; Xiaowen Pan; Yanfeng Zhou; Xijun Xu; Qi Zhang; Xiao-Ming Ji; Weijun Wang; Defeng Xing; Nanqi Ren; et al. (Journal of Cleaner Production, 2023)

Flexural behavior and design methodology for bamboo scrimber-aluminum plate composite beams - Ye Sheng; Defeng Tu; Feiyu Liao; Yuxing Yang; Chenggen He; Wei Zhang; Cheng Meng (Engineering Structures, 2023)

Capsular polysaccharide mediates Streptococcus agalactiae to resist Nile tilapia macrophage phagocytosis - Yanjian Yang; Meng Chen; Zhelin Wu; Defeng Zhang; Huiyan Lin; Xiayi Wei; Biao Han; Zheng Guo; Jianmin Ye (Aquaculture, 2023)

Hexavalent chromium disrupts the skin barrier by targeting ROS-mediated mitochondrial pathway apoptosis in keratinocytes - Cheng Wang; Hongqi Shang; Shuyu Zhang; Xiangkun Wang; Defeng Liu; Mingyue Shen; Ning Li; Yunxuan Jiang; Kai Wei; Ruiliang Zhu (Chemico-Biological Interactions, 2023)

Enhanced orbit and baseline determination for formation-flying LEO satellites with spaceborne accelerometer measurements - Chunbo Wei; Kai Shao; Defeng Gu; Zheng Zhang; Jubo Zhu; Zicong An; Jian Wang (Journal of Geodesy, 2023)

Pathogenicity of duck circovirus and fowl adenovirus serotype 4 co-infection in Cherry Valley ducks - Mingyue Shen; Panpan Gao; Cheng Wang; Ning Li; Shuyu Zhang; Yunxuan Jiang; Defeng Liu; Baoyu Jia; Li Xu; Bohan Huang; Ruiliang Zhu; Kai Wei (Veterinary Microbiology, 2023)

Formation of PCDD/Fs, PCBs and HCl during catalytic combustion of chlorobenzene over supported transition metal (Cr, V and Cu) oxide catalysts - Defeng Xing; Sheng Wang; Yun Fan; Haijun Zhang; Ting Wang; Mingzhe Wang; Shudong Wang; Jiancheng Wang; Dahai Pan; Xueding Song (Journal of Environmental Chemical Engineering, 2023)

Comparative genomics studies on the stk gene family in vertebrates: From the bighead carp (Hypophthalmichthys nobilis) genome - Yang Mao; Defeng Li; Rongrong Chen; Caifeng Ma; Junzhi Xiong; Kebin Zhang (Fish & Shellfish Immunology, 2023)

A New Conditionally Immortalized Nile Tilapia (Oreochromis niloticus) Heart Cell Line: Establishment and Functional Characterization as a Promising Tool for Tilapia Myocarditis Studies - Yanghui Chen; Yuan Li; Dongneng Jiang; Defeng Zhang; Yu Huang; Jia Cai; Jichang Jian; Bei Wang (Fishes, 2023)
A new cell line named the tilapia heart cell line (TAH-11) was established from the heart of tilapia (Oreochromis niloticus) by enzymatic digestion and mechanical separation. The TAH-11 cell line has been stably subcultured for over 80 generations and resuscitated after being frozen in liquid nitrogen for six months, with exuberant cell growth. The optimal culture condition of TAH-11 is L-15 medium supplemented with 10% fetal bovine serum at 25 °C. Sequencing of the mitochondrial 18S rRNAs confirmed that TAH-11 cells were derived from the tilapia. TAH-11 was also identified as a myocardial cell line based on the mRNA expression of the troponin I, α-actin and myoglobin genes. Simultaneously, TAH-11 could be successfully transfected with the GFP reporter gene, suggesting that the TAH-11 cell line could be used for exogenous gene expression in vitro. The TAH-11 cells showed susceptibility to CGSIV, which was demonstrated by the presence of a severe cytopathic effect, suggesting that the TAH-11 cell line is an ideal tool for studying host–virus interaction and potential vaccines. In addition, the expression of inflammatory factors in TAH-11 cells can be remarkably induced following Streptococcus agalactiae or Streptococcus iniae. The present data lays a foundation to further explore the mechanism of how Streptococcus spp. causes tilapia myocarditis.

Do ectoparasites on fish gills “talk” with gut microbiota far away? - Lin Wang; Defeng Zhang; Jun Xie; Ouqin Chang; Qing Wang; Cunbin Shi; Fei Zhao; Hua Gong; Yan Ren; Najiah Musa; Kok Leong Lee; Houjun Pan (Aquaculture, 2023)

Mutations in surface‐sensing receptor WspA lock the Wsp signal transduction system into a constitutively active state - Anming Xu; Di Wang; Yunhao Wang; Li Zhang; Zhensheng Xie; Yifan Cui; Pramod Bhamse; Haiying Yu; Xue‐Xian Zhang; Defeng Li; Luyan Z. Ma (Environmental Microbiology, 2022)
Summary Pseudomonas aeruginosa rugose small‐colony variants (RSCVs) are frequently isolated from chronic infections, yet, they are rarely reported in environmental isolates. Here, during the comparative genomic analysis of two P . aeruginosa strains isolated from crude oil, we discovered a spontaneous in‐frame deletion, wspA Δ280–307 , which led to hyper‐biofilm and RSCV phenotypes. WspA is a homologue of methyl‐accepting chemotaxis proteins (MCPs) that senses surfaces to regulate biofilm formation by stimulating cyclic‐di‐guanosine monophosphate (c‐di‐GMP) synthesis through the Wsp system. However, the methylation sites of WspA have never been identified. In this study, we identified E280 and E294 of WspA as methylation sites. The wspA Δ280–307 mutation enabled the Wsp system to lock into a constitutively active state that is independent of regulation by methylation. The result is an enhanced production of c‐di‐GMP. Sequence alignment revealed three conserved repeat sequences within the amino acid residues 280–313 (aa280–313) region of WspA homologues, suggesting that a spontaneous deletion within this DNA encoding region was likely a result of intragenic recombination and that similar mutations might occur in several related bacterial genera. Our results provide a plausible explanation for the selection of RSCVs and a mechanism to confer a competitive advantage for P . aeruginosa in a crude‐oil environment.

Comparative Transcriptome Analysis of Spleen Reveals Potential Regulation of Genes and Immune Pathways Following Administration of Aeromonas salmonicida subsp. masoucida Vaccine in Atlantic Salmon (Salmo salar) - Qiang Fu; Yuqing Li; Hao Zhang; Min Cao; Lu Zhang; Chengbin Gao; Xin Cai; Defeng Chen; Ziying Yang; Jie Li; Ning Yang; Chao Li (Marine Biotechnology, 2022)

Falsigemmobacter faecalis gen. nov. sp. nov., isolated from faeces of Rhinopithecus roxellanae, and reclassification of Gemmobacter intermedius as Falsigemmobacter intermedius comb. nov - Guiding Li; Yi Jiang; Qinyuan Li; Xiu Chen; Longqian Jiang; Kun Zhang; Defeng An; Lei Lang; Li Han; Xueshi Huang; Chenglin Jiang (Archives of Microbiology, 2020)

Methylobacterium planium sp. nov., isolated from a lichen sample - Longqian Jiang; Defeng An; Xinyu Wang; Kun Zhang; Guiding Li; Lei Lang; Lisong Wang; Chenglin Jiang; Yi Jiang (Archives of Microbiology, 2020)

Oleic Acid Alleviates Cadmium-Induced Oxidative Damage in Rat by Its Radicals Scavenging Activity - Jingwen Wang; Yuanyuan Zhang; Zhijia Fang; Lijun Sun; Yaling Wang; Ying Liu; Defeng Xu; Fanghong Nie; Ravi Gooneratne (Biological Trace Element Research, 2019)

A Path-Planning Strategy for Unmanned Surface Vehicles Based on an Adaptive Hybrid Dynamic Stepsize and Target Attractive Force-RRT Algorithm - Zhen Zhang; Defeng Wu; Jiadong Gu; Fusheng Li (Journal of Marine Science and Engineering, 2019)
It is well known that path planning has always been an important study area for intelligent ships, especially for unmanned surface vehicles (USVs). Therefore, it is necessary to study the path-planning algorithm for USVs. As one of the basic algorithms for USV path planning, the rapidly-exploring random tree (RRT) is popular due to its simple structure, high speed and ease of modification. However, it also has some obvious drawbacks and problems. Designed to perfect defects of the basic RRT and improve the performance of USVs, an enhanced algorithm of path planning is proposed in this study, called the adaptive hybrid dynamic stepsize and target attractive force-RRT(AHDSTAF-RRT). The ability to pass through a narrow area and the forward speed in open areas of USVs are improved by adopting the AHDSTAF-RRT in comparison to the basic RRT algorithm. The improved algorithm is also applied to an actual gulf map for simulation experiments, and the experimental data is collected and organized. Simulation experiments show that the proposed AHDSTAF-RRT in this paper outperforms several existing RRT algorithms, both in terms of path length and calculating speed.

Capsular polysaccharide of Streptococcus agalactiae is an essential virulence factor for infection in Nile tilapia ( Oreochromis niloticus Linn.) - Defeng Zhang; Xiaoli Ke; Zhigang Liu; Jianmeng Cao; Youlu Su; Maixin Lu; Fengying Gao; Miao Wang; Mengmeng Yi; Fengling Qin (Journal of Fish Diseases, 2019)
Streptococcus agalactiae (Group B Streptococcus , GBS) is associated with diverse diseases in aquatic animals. The capsule polysaccharide (CPS) encoded by the cps gene cluster is the major virulence factor of S. agalactiae ; however, limited information is available regarding the pathogenic role of the CPS of serotype Ia piscine GBS strains in fish. Here, a non‐encapsulated mutant (Δ cps ) was constructed by insertional mutagenesis of the cps gene cluster. Mutant pathogenicity was evaluated in vitro based on the killing of whole blood from tilapia, in vivo infections, measuring mutant survival in tilapia spleen tissues and pathological analysis. Compared to wild‐type (WT) GBS strain, the Δ cps mutant had lower resistance to fresh tilapia whole blood in vitro ( p 0.01), and more easily cleared in tilapia spleen tissue, and was highly attenuated in tilapia and zebrafish. Additionally, compared to the Δ cps mutant, numerous GBS strains and severe tissue necrosis were observed in the tilapia spleen tissue infected with WT strains. These results indicated that the CPS is essential for GBS pathogenicity and may serve as a target for attenuation in vaccine development. Gaining a better understanding of the role, the GBS pathogenicity in fish will provide insight into related pathogenesis and host–pathogen interactions.

Streptococcus agalactiae from tilapia (Oreochromis sp.) transmitted to a new host, bighead carp (Aristichthys nobilis), in China - Defeng Zhang; Xiaoli Ke; Lihui Liu; Maixin Lu; Cunbin Shi; Zhigang Liu (Aquaculture International, 2018)

Differential roles for ArcA and ArcB homologues in swarming motility in Serratia marcescens FS14 - Xiaolan Zhang; Defeng Wu; Tengfei Guo; Tingting Ran; Weiwu Wang; Dongqing Xu (Antonie van Leeuwenhoek, 2018)

Controllable synthesis Fe3O4@POHABA core-shell nanostructure as high-performance recyclable bifunctional magnetic antimicrobial agent - Zhijia Zhang; Defeng Xing; Xin Zhao; Xiaojun Han (Environmental Science and Pollution Research, 2017)

Root morphology in response to nitrogen supply in mid-season indica rice cultivars released in different decades - Yikai Zhang; Huizhe Chen; Yuping Zhang; Jing Xiang; Guangmei Ji; Defeng Zhu (Science China Life Sciences, 2017)

Modeling the effects of different conditions on the inhibitory activity of antimicrobial lipopeptide (AMPNT-6) against Staphylococcus aureus growth and enterotoxin production in shrimp meat - Ning Zhang; Yuehua Pu; Lijun Sun; Yaling Wang; Qi Deng; Defeng Xu; Ying Liu; Malik Hussain; Ravi Gooneratne (Aquaculture International, 2017)

Quantitative characterization and comprehensive evaluation of regional water resources using the Three Red Lines method - Zheng Zang; Xinqing Zou; Xu Xi; Yu Zhang; Defeng Zheng; Caizhi Sun (Journal of Geographical Sciences, 2016)

The structural characteristics, age of origin, and tectonic attribute of the Erguna Fault, NE China - Han Zheng; XiaoMeng Sun; DeFeng Zhu; JingXiong Tian; Song He; YingDe Wang; XuQing Zhang (Science China Earth Sciences, 2015)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Empirical research on carrying capacity of human settlement system in Dalian City, Liaoning Province, China - Defeng Zheng; Yu Zhang; Zheng Zang; Caizhi Sun (Chinese Geographical Science, 2015)

Age assignment and geological significance of the “Budate Group” in the Hailar Basin - Qi’An Meng; ChuanBiao Wan; DeFeng Zhu; YanLong Zhang; WenChun Ge; FuYuan Wu (Science China Earth Sciences, 2013)

Dietary salt modulates the sodium chloride cotransporter expression likely through an aldosterone-mediated WNK4-ERK1/2 signaling pathway - Lingyun Lai; Xiuyan Feng; Defeng Liu; Jing Chen; Yiqian Zhang; Bowen Niu; Yong Gu; Hui Cai (Pflügers Archiv - European Journal of Physiology, 2012)